Leadership Strategy: Implementation of Religious-Based Character Education Through Multicultural Learning After the Covid-19 Pandemic - Huda, Syamsul; Ridwanulloh, M. Ubaidillah; Aulia, Astain Kusnul; Prasetiyo, Andika Eko (Psikis : Jurnal Psikologi Islami, 2024)
This study aims to determine the right leadership strategy to identify and describe the implementation of character education with various backgrounds of students after the covid-19 pandemic. By applying multicultural learning, it is hoped that it will be able to teach theoretical concepts about various good or bad characters, but rather try to influence the character of good students. in the direction the teacher expects. This study uses an ex post facto qualitative design with data collection through observation and case studies. Sources of data obtained from informants, namely principals, teachers, students, and parents. The result of the research is that the implementation of character education for students with various backgrounds is carried out by getting used to good characters who are accustomed to religious activities and the teacher gives examples of good character (respect for teachers, fellow students and younger siblings) in everyday life. In addition, it also gets used to saying greetings and smiling when meeting anyone, such as teachers, friends, and other people outside of school. There is an additional excellent program, namely the compulsory Koran program for every student. Even with the Covid-19 condition, the portion of character education has not decreased as face-to-face schools, but has increased. The teacher monitors the character development of students starting from waking up in the morning until going back to sleep the next night. The role of the principal is very supportive of the character education that has been implemented in schools. Not only that, with the covid-19 pandemic, school principals made a policy by providing quota pulses to be used to communicate with students so that the habit of good character continues to run even at home.